Early-Stage Primary Anti-inflammatory Therapy Enhances the Regenerative Efficacy of Platelet-Rich Plasma in a Rabbit Achilles Tendinopathy Model. Issue 12 (October 2021) - Ruan, Dengfeng; Tang, Chenqi; Fei, Yang; Qian, Shengjun; Xiang, Xinyu; Xu, Jialu; Huang, Zizhan; Chen, Xiao; Chin Heng, Boon; Yin, Zi; Chen, Weishan; Liu, Wanlu; et al.
Background: Tendinopathy is a pervasive clinical problem that afflicts both athletes and the general public. Although the inflammatory changes in tendinopathy are well characterized, how the therapeutic effects of platelet-rich plasma (PRP) on tendinopathy are being modulated by the inflammatory environment is not well defined. Purpose/Hypothesis: In this study, we aimed to compare the therapeutic effects of PRP alone versus a combination of PRP with a primary glucocorticoid (GC) injection at the early stage of tendinopathy. We hypothesized that PRP treatment could promote better tendon regeneration through the suppression of inflammation with GC. Study Design: Controlled laboratory study. Methods: The gene expression profile of tendon stem/progenitor cells (TSPCs) cultured with PRP was analyzed with RNA sequencing. To evaluate the cell viability, senescence, and apoptosis of TSPCs under different conditions, TSPCs were treated with 0.1 mg/mL triamcinolone acetonide (TA) and/or 10% PRP in an IL1B–induced inflammatory environment. To further verify the effects of the sequential therapy of GCs and PRP, an early tendinopathy animal model was established through a local injection of collagenase in the rabbit Achilles tendon. The tendinopathy model was then treated with isopycnic normal saline (NS group), TA (TA group), PRP (PRP group), or TA and PRP successively (TA+PRP group). At 8 weeks after treatment, the tendons were assessed with magnetic resonance imaging (MRI), histological examination, transmission electron microscopy (TEM), and mechanical testing. Results: Gene Ontology enrichment analysis indicated that PRP treatment of TPSCs induced an inflammatory response, regulated cell migration, and remodeled the extracellular matrix. Compared with the sole use of PRP, successive treatment with TA followed by PRP yielded similar results in cell viability and senescence but less cell apoptosis in vitro. In vivo experiments demonstrated that the TA+PRP group achieved significantly better tendon regeneration, as confirmed by MRI, histological examination, TEM, and mechanical testing. Conclusion: This study showed that the primary use of GCs did not exert any obvious deleterious side effects on the treated tendon but instead enhanced the regenerative effects of PRP in early inflammatory tendinopathy. Clinical Relevance: The sequential therapy of GCs followed by PRP provides a promising treatment strategy for tendinopathy in clinical practice. PRP combined with the primary use of GCs appears to promote tendon regeneration in early inflammatory tendinopathy.